LncRNA SNHG5 promotes cervical cancer progression by regulating the miR-132/SOX4 pathway. (17th February 2021) - Zhang, Liqin; Wu, Xiaoming; Li, Yue; Teng, Xianlin; Zou, Libo; Yu, Beiwei
Abstract: Background: The long non-coding RNA (lncRNA) small nucleolar RNA host gene 5 (SNHG5) has been verified as a crucial regulator in many types of tumours but not clear in cervical cancer (CC). This study aims to investigate the effect and further mechanisms of lncRNA SNHG5 in CC. Methods: The expression of SNHG5 and miR-132, as well as SOX4 (sex-determining region Y-box 4) mRNA expression were determined by quantitative real-time PCR (qRT-PCR). The protein level of SOX4 and epithelial-mesenchymal transition (EMT)-related proteins were evaluated by western blot. Then, Edu and Transwell assay were performed to assess the proliferation, migration and invasion of CC cells. RNA immunoprecipitation (RIP) and RNA pull-down assay were conducted to explore the relationship between SNHG5 and miR-132. Results: SNHG5 and SOX4 were upregulated, and miR-132 was downregulated in CC tissues and cell lines. SNHG5 was positively correlated with FIGO stage ( p = .003) and lymph node metastasis ( p = .001). Pearson's correlation analysis conveyed that SNHG5 was positively correlated with SOX4, and miR-132 was negatively correlated with SOX4 and SNHG5. Knockdown of SNHG5 in vitro reduced CC cell proliferation, migration and invasion through regulating miR-132. Moreover, overexpression of miR-132 restrained CC cell proliferation, migration, and invasion through targeting SOX4, and SNHG5 enhanced SOX4 expression via negatively regulating miR-132. Conclusion: SNHG5 promotes SOX4 expression to accelerate CC cell proliferation, migration and invasion through negatively regulating miR-132.